(Re)moving waste: caste, spaces, and materials in Delhi - Agarwal, A (2022)
Delhi is faced with a burgeoning growth of discarded materials—commonly referred to as waste. This rapid increase is characterised by chaos and disorder in the management of waste. This thesis examines the disorder and its effects through the lens of materials, spaces, time, people, and infrastructures involved in the flow of waste through the city. I focus on three waste-related sites in Delhi—Balmiki colonies, the Bhalswa landfill, and recycling units in north-west Delhi—and show how discarded materials acquire different meanings in different contexts and subsequently shape the caste-, class-, and gender- based social relations and the social and economic value associated with waste work and waste workers. I demonstrate this by focusing on the technocratic infrastructure of waste management and by examining the human and caste-based infrastructure of waste management. I show how the growing privatisation of the waste management infrastructure and the use of technology alongside the Clean India Campaign are projected as symbols of modernity and cleanliness and are used to invisibilise the human and environmental dimensions of the waste crisis for political and economic profit. Simultaneously, I focus on waste workers—municipal sanitation workers, public private partnership-led garbage collectors, informal waste pickers, and recyclers—to demonstrate the varying nature of stigma, discrimination, and evaluation of waste work and waste workers. I illustrate how urban marginality has pushed not only Scheduled Caste communities’ workers but also many non-Scheduled Caste communities, such as Muslim and Hindu OBCs, into waste work, transforming their social relations and caste hierarchies at a micro level. Furthermore, I examine how the value of waste work varies from being reproductive (city’s livability) to productive (generating exchange value in waste materials), across different spatio-temporal axes and value chains, and how that shapes the way waste workers perceive themselves and their work.